The variation of insulin like growth factor 2 maker is associated with growth traits in Thai native (Kradon) pigs - Kessara Ampaporn; Rattikan Suwannasing; Pitchayanipa Phongphanich; Supanon Tunim; Monchai Duangjinda (Animal Bioscience, 2023)
Objective This study was conducted to investigate polymorphisms of the melanocortin-4 receptor (MC4R) and insulin like growth factor 2 (IGF2) genes and to evaluate the growth traits affected by such polymorphisms in Thai native (Kradon) pigs. Methods Blood samples and productive data from 91 Kradon pigs were collected. DNA was extracted and quantified, the IGF2 and MC4R genes were amplified, and the polymerase chain reaction (PCR) produces were digested using the PCR-restriction fragment length polymorphism (PCR-RFLP) technique. Genotyping was performed, and the association between genotypes and growth traits on the birth and weaning weights were evaluated. Results The IGF2 intron7 g.162G>C variations in Kradon pigs were found in three genotypes: i) GG, ii) GC, and iii) CC. The GG genotype frequency was the highest followed by the GC and CC genotypes. The frequencies of the G and C alleles were 0.703 and 0.297, respectively. The MC4R genotype was found in only one genotype (GG). The IGF2 gene pattern was not associated with birth weight traits, whereas the IGF2 gene pattern was related to the weaning weight trait in Kradon pigs. Pigs with the CC and GC genotypes had higher weaning weights than ones with the GG genotype (p<0.001). Conclusion Thai native Kradon pigs with the CC and GC genotypes of the IGF2 gene have higher weaning weights than pigs with the GG genotype.